Sosialisasi Penerapan Apartemen Ikan sebagai Upaya Peningkatan Ketahanan Pangan Masyarakat Pesisir di Bancaran - Mertiara Ratih Terry Laksani; Febi Ayu Pramithasari; Fauzan Arrofiqi (Yayasan Literasi Sains Indonesia, 2025)
The socialization program for implementing fish apartments in Bancaran was developed to enhance food security and strengthen the capacity of local fishing communities. Degradation of coastal ecosystems, declining fish catches, and increasing exploitation have reduced fish availability, affecting income stability and lowering fish stocks. Fish apartments are introduced as a solution to increase habitat complexity, provide nursery and spawning areas, attract fish aggregations, and ultimately improve aquatic productivity. The program applied a community empowerment approach, beginning with the introduction of the fish apartment concept, followed by discussions on structural designs and agreement on suitable installation sites. Activities were conducted at the Bancaran Village Hall and involved 22 participants, 80% of whom were fishers, along with representatives from other coastal fisheries sectors. Additional participants included DP2KP, TNI, POLRI, and local traders. Visual presentations and interactive discussions were used as the primary methods. Program effectiveness was evaluated through pre- and post-tests to measure understanding and perceptions. Results showed a substantial increase in knowledge of fish apartment structures and benefits, rising from 18% to 100%. Perception also improved, with “strongly agree” responses increasing from 86.4% to 100%. These outcomes reflect strong community support and provide a solid foundation for implementing the technology to enhance fisheries productivity and strengthen sustainable food security in Bancaran’s coastal community.